2018
DOI: 10.1186/s12931-018-0888-7
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-based clusters in current smokers of the COPD cohort associate with clinical characteristics: the SubPopulations and Intermediate Outcome Measures in COPD Study (SPIROMICS)

Abstract: BackgroundClassification of COPD is usually based on the severity of airflow, which may not sensitively differentiate subpopulations. Using a multiscale imaging-based cluster analysis (MICA), we aim to identify subpopulations for current smokers with COPD.MethodsAmong the SPIROMICS subjects, we analyzed computed tomography images at total lung capacity (TLC) and residual volume (RV) of 284 current smokers. Functional variables were derived from registration of TLC and RV images, e.g. functional small airways d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
(46 reference statements)
0
29
0
Order By: Relevance
“…We analyzed former smokers independently from current smokers because smoking status may have significant effect on lung density, and cessation of smoking can be deemed as an effective intervention (32), resulting in different progression patterns. The imagingbased variables were also employed in cross-sectional cluster analysis (13,14) and these variables were found to be a sensitive means of differentiating subgroups in COPD and asthma cohorts (11,14). However, evidence has shown that the disease progression depends on the subject's current stage and even at the same disease stage the progression patterns may differ (3).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We analyzed former smokers independently from current smokers because smoking status may have significant effect on lung density, and cessation of smoking can be deemed as an effective intervention (32), resulting in different progression patterns. The imagingbased variables were also employed in cross-sectional cluster analysis (13,14) and these variables were found to be a sensitive means of differentiating subgroups in COPD and asthma cohorts (11,14). However, evidence has shown that the disease progression depends on the subject's current stage and even at the same disease stage the progression patterns may differ (3).…”
Section: Discussionmentioning
confidence: 99%
“…The separate quantification of emphysema and small airway disease can dissociate the emphysematous region(s) from the air-trapped region(s) (3). fSAD% and Emph% with the respective air-fraction threshold of 90% and 98.5% were employed to eliminate the effects of scanners (13)(14)(15). Tissue fractions at TLC (β tissue TLC ) and at RV (β tissue RV ) (14) were introduced to measure the proportion of tissue volume in each voxel for detection of tissue destruction and inflammation.…”
Section: Derivation Of Qct Imaging-based Metricsmentioning
confidence: 99%
See 3 more Smart Citations